An overview of natural products that modulate the expression of non-coding RNAs involved in oxidative stress and inflammation-associated disorders - Ngum, Jubilate Afuoti; Tatang, Fabrice Junior; Toumeni, Michelle Hako; Nguengo, Sarah Ngate; Simo, Ulrich Stephane Fotso; Mezajou, Cybelle Fodieu; Kameni, Charleine; Ngongang, Natacha Njike; Tchinda, Maxwell Fofou; Dongho Dongmo, Fabrice Fabien; Akami, Mazarin; Ngane Ngono, Annie Rosalie; et al. (Frontiers in Pharmacology, 2023)
Oxidative stress is a state in which oxidants are produced in excess in the body’s tissues and cells, resulting in a biological imbalance amid the generation of reactive oxygen and nitrogen species (RONS) from redox reactions. In case of insufficient antioxidants to balance, the immune system triggers signalling cascades to mount inflammatory responses. Oxidative stress can have deleterious effects on major macromolecules such as lipids, proteins, and nucleic acids, hence, Oxidative stress and inflammation are among the multiple factors contributing to the etiology of several disorders such as diabetes, cancers, and cardiovascular diseases. Non-coding RNAs (ncRNAs) which were once referred to as dark matter have been found to function as key regulators of gene expression through different mechanisms. They have dynamic roles in the onset and development of inflammatory and oxidative stress-related diseases, therefore, are potential targets for the control of those diseases One way of controlling those diseases is through the use of Natural products, a rich source of antioxidants that have drawn attention with several studies showing their involvement in combating chronic diseases given their enormous gains, low side effects, and toxicity. In this review we highlighted the natural products that have been reported to target ncRNAs as mediators of their biological effects on several inflammation-associated disorders. Those natural products include Baicalein, Tanshinone IIA, Geniposide, Carvacrol/Thymol, Triptolide, Oleacein, Curcumin, Resveratrol, Solarmargine, Allicin, aqueous extract or pulp of Açai, Quercetin, and Genisten. We also draw attention to some other compounds including Zanthoxylum bungeanum, Canna genus rhizome, Fuzi-ganjiang herb pair, Aronia melanocarpa, Peppermint, and Gingerol that are effective against oxidative stress and inflammation-related disorders, however, have no known effect on ncRNAs. Lastly, we touched on the many ncRNAs that were found to play a role in oxidative stress and inflammation-related disorders , but have not yet been investigated as targets of a natural product. Shedding more light into these two last points of shadow will be of great interest in the valorization of natural compounds in the control and therapy of oxidative stress- and inflammation-associated disorders.